Biologia populacional e produção secundária de Olivancillaria vesica vesica (Gmelin, 1791) (Gastropoda : Olividae) na praia da Restinga da Marambaia, RJ - Caetano, Carlos Henrique Soares (2001)
Monthly samples were carried out between June 1998 and August 2000 in Restinga da Marambaia beach, RJ with the purpose of study the population biology and secondary production of Olivancillaria vesica vesica (Mollusca: Gastropoda: Olividae). Specimens were handmade collected in two transects and the lenght and width of your shells were measured in the field. Growth and mortality was estimated using computer based methods of lenght-frequency data contained in FISAT package. Life span was estimated by inverse von Bertalanffy growth equation considering tmax as the 95% of the asymptotic lenght. Hynes and Crisp 3A methods were utilized for the calculation of secondary production. Highest population densities were observed during winter (September 1998 and 1999) and autumn (June 2000). Parameters estimated indicate moderated seasonal oscillations in growth with the slowest growth rates occuring in late summer (1st year) and spring (2nd year). Life span varied between 4.28 and 4.99 years. Secondary production estimatives varied between 0.142 and 0.213g AFDW m-2 year -1. The sex ratio was 1.18 for males. Occurence of imposex in females of this species was observed.